Technology Research and Development for Environmental Management - With Specific Reference to Malaysia - B. Ghin Yeoh; Ahmad Zaharudin Idrus; K.S Ong (ASEAN Journal on Science and Technology for Development, 1988)
Technology Research and Development for Environmental Management - With Specific Reference to Malaysia